Gaining insight into the implementation of an e-learning smoking cessation course in Latin American countries. - Vides-Porras, Ana; Cáceres, Paula; Company, Assumpta; Guillen, Olga; Arrien, Martha Alicia; Castellano, Yolanda; Margalef, Mercè; Yantuche, Wendy; Fernández, Esteve; Martínez, Cristina; Project, the Group of Hospital Coordinators in the Fruitful (Health Promotion International, 2021)
Continuous medical education focused on health problems emerging in low- and middle-income countries (LMICs) is scarce. Although tobacco consumption is increasing in LMICs, there is a lack of tobacco cessation training programs in these countries. To promote smoking cessation interventions in Bolivia, Guatemala and Paraguay, we adapted an e-learning program developed in Catalonia (Spain). This process evaluation study reports on reach, dose and satisfaction of participants with the course, as well as the contextual factors of its application. We conducted a multiple method evaluation, which included a survey and several focus groups, each one specific to the same type of healthcare professional (nurses, doctors, other professionals). Two hundred and ninety-two participants registered into the online course. The motivation for undertaking the course was different between doctors and nurses. The main sources of difficulty in enrolling and finishing the course were the technical problems experienced when accessing the platform, and lack of acquaintance with computers and the Internet in general. Our results show that implementing e-learning education in hospitals from LMICs is feasible, especially when there are similarities between participating countries and the country in which the original program was developed. However, several elements such as strong organizational commitment, technical support and resources and adequate communication channels should be provided to facilitate enrollment and training completion. Efforts to improve Internet access should be made to avoid jeopardizing students' motivation to enroll and complete online training.